Sarcopenia and Orthostatic Hypotension: Investigating the Underlying Haemodynamics - Duggan, Eoin (Trinity College Dublin. School of Medicine. Discipline of Medical Gerontology, 2025)
The ageing population worldwide is both one of the greatest successes of modern humanity and one of its greatest challenges. These challenges are numerous and include the geriatric syndromes of sarcopenia and orthostatic hypotension (OH). These two geriatric syndromes are increasingly recognised as important drivers of adverse outcomes in older adults. There is reason to suggest a pathophysiological link between the two conditions in the form of the skeletal muscle pump (SMP) of the lower limbs. The SMP is thought to aid venous return during standing via rhythmic activity of the skeletal limb muscles. One might hypothesise that the effects of sarcopenia on the muscles of the lower limbs might impair the SMP, increasing the risk of OH. While the relationship between sarcopenia and OH has previously been investigated in a small number of studies, the early recovery of blood pressure (BP) on standing and the haemodynamic mechanisms underlying these relationships have not. In addition, the contribution of the SMP to orthostatic BP recovery and maintenance is poorly understood. This doctoral investigation sought to examine the relationship between sarcopenia, BP recovery after standing and OH in people aged ≥ 50 years. It aimed to examine the haemodynamic factors underlying these relationships and to determine, in particular, any indirect evidence for the role of the SMP. It consisted of three independent studies: Study I, a population cohort from The Irish Longitudinal Study on Ageing (TILDA) (N = 2858); Study II, a clinical sample recruited from the Falls and Syncope Unit at St. James’s Hospital Dublin (N = 109); and Study III a physiological sample of healthy community-dwelling older adults (N = 31). Study I found that probable sarcopenia was independently associated with a significantly attenuated recovery of BP up to 30-40 s after standing, but not thereafter. Those defined as having probable sarcopenia by hand grip strength (HGS) criteria had a larger and longer BP attenuation compared to those defined by 5-chair stands test (5CST) criteria. In TILDA, probable sarcopenia with OH had a higher odds ratio for future falls compared to OH or sarcopenia alone. Study II-A expanded these findings to sarcopenia confirmed by bioelectrical impedance analysis (BIA), finding that both probable sarcopenia and sarcopenia, with an incremental effect, were independently associated with an attenuated BP recovery rate in the 10–20 s period after standing. The results were independent of heart rate (HR), indicating the need to examine underlying haemodynamic parameters. Study II-B investigated the haemodynamic factors underlying the relationship between sarcopenia and BP recovery after standing. It found that the mean arterial pressure (MAP) changes after standing appeared to be driven by a blunted initial peak and a slower reduction from the peak of cardiac output (CO) in the sarcopenia group. This was followed by an attenuated recovery of total peripheral resistance (TPR) from nadir after standing in the sarcopenia group. The CO finding appeared to be driven by stroke volume (SV) rather than HR. Given that MAP =CO ×TPR and CO =SV ×HR, these findings suggested that sarcopenia could reduce SV via reduction of SMP (preload), but also impair TPR response via reduced muscle sympathetic nervous activity, or potentially further reduce CO in association with reduced heart contractility in this clinical sample (“cardiosarcopenia”). Study III found that in a comparatively healthier sample, measures of muscle strength (again, HGS but not 5CST) and mass (by BIA and also by ultrasound-measured muscle thickness) were associated with BP recovery early after standing (10–30 s). HGS was associated with change in CO in the 10–20 s period (again, SV but not HR), and with change in TPR at 20–30 s. In an effort to further evidence the plausible role of the SMP during contemporaneous muscle activation, I found that early BP recovery after standing was associated with changes in haemoglobin concentration in the thigh as measured by near-infrared spectroscopy during the 10–20 s period, but not with thigh muscle activation as measured by surface electromyography (EMG). Furthermore, the effects of physical counterpressure manoeuvres (PCMs) were also studied in this sample, and during the latter changes in BP were associated with change in TPR, but not CO. Overall, sarcopenia appeared to be related to an attenuated BP recovery early after standing. While the mechanisms underlying this relationship are not fully characterised, the SMP likely plays a role through effects on venous return and stroke volume, in addition to sympathetic nervous system activation. The latter seemed more important that the former during PCMs. Sarcopenia could contribute to falls by impairing BP recovery after standing, as well as through traditionally considered effects such as impairment of gait and balance. Unlike some other risk factors for OH, sarcopenia is potentially reversible. Therefore, it is important to screen for sarcopenia in falls clinics, especially in patients with OH. Future research on the effects of sarcopenia interventions on orthostatic BP recovery is needed.
APPROVED
Keywords: sarcopenia; orthostatic hypotension; falls; frailty; postural hypotension; orthostasis; orthostatic haemodynamics; muscle strength; muscle mass; blood pressure recovery